Negative Emotion Impairs Conflict-Driven Executive Control - Padmala, Srikanth; Bauer, Andrew; Pessoa, Luiz (Frontiers in Psychology, 2011)
Cognition and emotion interact in important ways to shape ongoing behaviors. In this study, we investigated the interaction between conflict-driven executive control adjustments and emotion during a face-word Stroop-like paradigm. Neutral and negative images were employed to manipulate emotion. We were particularly interested in contrasting two hypotheses of the impact of emotion on conflict adaptation effects. On the one hand, resource accounts of cognitive-emotional interactions predict that behavioral adjustments following incongruent trials would be decreased when participants also have to process a negative stimulus. On the other hand, affect regulation models predict that negative emotion should increase behavioral adjustments. We found that task-irrelevant negative stimuli significantly reduced conflict-driven control effects (i.e., conflict adaptation) compared to neutral images. We interpret the findings in terms of shared resources between proactive control mechanisms and emotional processing. Our findings demonstrate that emotion interacts with executive mechanisms responsible for dynamic behavioral adjustments that are tied to environmental demands, a central facet of flexible, goal-directed behavior.